2002
DOI: 10.1016/s0301-472x(02)00869-x
|View full text |Cite
|
Sign up to set email alerts
|

Multipotent progenitor cells can be isolated from postnatal murine bone marrow, muscle, and brain

Abstract: This study shows that cells with MAPC characteristics can be isolated not only from BM, but also from brain and muscle tissue. Whether MAPC originally derived from BM are circulating or all organs contain stem cells with MAPC characteristics currently is being studied. Presence of MAPC in multiple tissues may help explain the "plasticity" found in multiple adult tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
546
3
20

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 784 publications
(588 citation statements)
references
References 48 publications
12
546
3
20
Order By: Relevance
“…In addition to satellite cells that were previously thought to be the only cell source for muscle regeneration, other cell types, such as SP cells and MAPCs in various tissues, possibly originating from the vascular endothelium, may also contribute to muscle repair. 17,19,35,36 We have previously shown that lentiviral vectors mediate microdystrophin gene transfer to mdx muscle SP cells, and that transduced SP cells can deliver dystrophin genes to regenerating mdx muscle fibers following tail vein transplantation. 36 Kobinger et al 15 showed that lentiviral vectors can transduce satellite cells in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to satellite cells that were previously thought to be the only cell source for muscle regeneration, other cell types, such as SP cells and MAPCs in various tissues, possibly originating from the vascular endothelium, may also contribute to muscle repair. 17,19,35,36 We have previously shown that lentiviral vectors mediate microdystrophin gene transfer to mdx muscle SP cells, and that transduced SP cells can deliver dystrophin genes to regenerating mdx muscle fibers following tail vein transplantation. 36 Kobinger et al 15 showed that lentiviral vectors can transduce satellite cells in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse MAPCs from bone marrow and skeletal muscle possess myogenic potential. 19 We examined whether lentiviral vectors could effectively transduce mouse MAPCs. MAPCs isolated from wild-type mouse skeletal muscle were transduced with L-MSCV-eGFP vectors at an MOI of 10.…”
Section: Genetically Modified MDX Myoblasts Retain Myogenic Potentialmentioning
confidence: 99%
See 2 more Smart Citations
“…A population of highly plastic, adult derived bone marrow cells, referred to as mulitpotent adult progenitor cells (MAPC) can be grown in vitro from the post-natal marrow of mice, rats and humans [14]. Unlike MSC, MAPC can be cultured indefinitely in a relatively nutrient-poor medium.…”
Section: Multipotent Adult Progenitor Cellsmentioning
confidence: 99%